Bosnian King Nicholas of Ilok and his Pilgrimage to Rome (1475) : A Probe into the Daily Life of Medieval Pilgrims - Hlavačková, Miriam (East Central and Eastern Europe in the Middle Ages, 450-1450, 2026)
"You do not see a city when you see Rome, but a piece of heaven," wrote the author of a medieval guidebook. But how did pilgrims find their way to Rome without getting lost? Where did they sleep and what did they eat? Why did both the rich and the poor set out on such long and dangerous journeys? The author of this volume explores the everyday hardships and joys of medieval pilgrims through the eyes of Nicholas of Ilok, King of Bosnia. This unique perspective offers new insights into medieval mobility and illustrates that pilgrimage was not only an expression of personal piety, but also a form of diplomacy and European cultural exchange.